On the morphology and life-history of Hemiurus luehei Odhner, 1905 (Digenea: Hemiuridae). - Køie, M. (Journal of Helminthology, 1990)
Previously undescribed cystophorous cercariae which develop in sporocyst germinal sacs in the tectibranch opisthobranch Philine denticulata (Adams) are shown to be cercariae of Hemiurus luehei Odhner, 1905 (Hemiuridae), a common stomach parasite of clupeid and salmonid fishes off the Atlantic coast of Europe, in the Baltic and the Mediterranean Sea. The free-swimming cercariae are seized by calanoid copepods. Temora longicornis (Müller) and Acartia tonsa Dana acted as suitable experimental intermediate hosts. Pressure by the copepod mouth appendages causes delivery tube eversion and the injection of the cercarcial body into the haemocoel. Sagitta sp. was found naturally infected with a metacercaria of H. luehei. The cystophorous cercaria and metacercaria are described using light and scanning electron microscopy. Adults from herring were examined under the stereoscan electron microscope.